2017
DOI: 10.1002/ajmg.a.38340
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Xeroderma pigmentosum variant in a young patient with two novel mutations in the POLH gene

Abstract: We describe the characterization of Xeroderma Pigmentosum variant (XPV) in a young Caucasian patient with phototype I, who exhibited a high sensitivity to sunburn and multiple cutaneous tumors at the age of 15 years. Two novel mutations in the POLH gene, which encodes the translesion DNA polymerase η, with loss of function due to two independent exon skippings, are reported to be associated as a compound heterozygous state in the patient. Western blot analysis performed on proteins from dermal fibroblasts deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…35 Inactivating variants of POLH, which encodes the translesion DNA polymerase η are responsible for Xeroderma Pigmentosum, a rare recessive syndrome associated with hypersensitivity to sunlight and a high frequency of skin cancers at an early age. 36,37 Of note, a germline POLH MV (c.2074A>G) was identified by WES in a Lebanese BC-prone family 38 but this variant, predicted to be benign by various tools, was not found in our population. RTEL1 encodes the regulator of telomere elongation helicase 1, which is essential for telomere maintenance and regulation of homologous recombination.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…35 Inactivating variants of POLH, which encodes the translesion DNA polymerase η are responsible for Xeroderma Pigmentosum, a rare recessive syndrome associated with hypersensitivity to sunlight and a high frequency of skin cancers at an early age. 36,37 Of note, a germline POLH MV (c.2074A>G) was identified by WES in a Lebanese BC-prone family 38 but this variant, predicted to be benign by various tools, was not found in our population. RTEL1 encodes the regulator of telomere elongation helicase 1, which is essential for telomere maintenance and regulation of homologous recombination.…”
Section: Discussionmentioning
confidence: 66%
“…Transcriptome analysis of BC cell lines and tissue identified somatic recurrent rearrangements involving MAST1 and over‐expression of the resulting gene fusion . Inactivating variants of POLH , which encodes the translesion DNA polymerase η are responsible for Xeroderma Pigmentosum, a rare recessive syndrome associated with hypersensitivity to sunlight and a high frequency of skin cancers at an early age . Of note, a germline POLH MV (c.2074A>G) was identified by WES in a Lebanese BC‐prone family but this variant, predicted to be benign by various tools, was not found in our population.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies also demonstrated that Polη was particularly efficient at bypassing ultraviolet (UV) radiation-induced cyclobutane pyrimidine dimers, and could accurately insert an A opposite to the T of the dimer (20). Humans that lack Polη suffer from xeroderma pigmentosum variant, resulting in an extreme sensitivity to UV radiation (21). Polη can replicate 8-oxoguanine lesions efficiently and accurately by inserting a C opposite to the damage site (22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also demonstrated that Pol was particularly efficient at bypassing UV radiation-induced cyclobutane pyrimidine dimers and could accurately insert an A opposite of the T of the dimer (20). Humans that lack Pol suffer from xeroderma pigmentosum variant, resulting in an extreme sensitivity to UV radiation (21). Pol can replicate 8-oxoguanine lesions efficiently and accurately by inserting a C opposite of the damage site (22).…”
mentioning
confidence: 99%